Perencanaan Pembangunan Infrastruktur Berbasis SDGs (Pilar Lingkungan Hidup) di Kabupaten Bojonegoro - Laili, Tarjibu Azizatul (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2024)
This research aims to find out and analyze how the SDGs-based development planning system on the environmental development pillar. This research uses descriptive qualitative research methods, data collected through interviews and observations at the Regional Development Planning Agency (BAPPEDA), the Environmental Agency (DLH), and several communities directly affected by infrastructure development in Bojonegoro Regency. The data analysis method was carried out using the Miles and Huberman method, which has three stages of analysis. The theory of the planning process proposed by Berry (1993) in Mahi and Trigunarso (2017) was used in this study. The results showed that infrastructure development planning has been carried out in Bojonegoro Regency, but the existence of infrastructure development programs shows that these programs affect environmental conditions, especially affecting the proportion of green open space (RTH). Overall, the infrastructure development plan in Bojonegoro Regency has not fulfilled the perspectives in the SDGs, especially in the environmental development pillar.